2011
DOI: 10.1159/000324263
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Patients with Primary Signet-Ring Cell Carcinoma of the Urinary Bladder

Abstract: Objective: The aim of this study was to examine the epidemiology, natural history, treatment pattern and predictors of long-term survival of patients with signet-ring cell carcinoma (SRCC) of the urinary bladder based on the analysis of the national Surveillance, Epidemiology, and End Results (SEER) database. Methods and Results: In total, 230 patients with pathologically confirmed SRCC of the urinary bladder were identified between 1973 and 2004. The mean age was 65 ± 13 years. Overall, 75.7% of the patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…The proportion of the SRCC component is associated with advanced-stage disease and worse outcomes. Its invasion pattern could spread laterally and widely without protruding through the surface (18). Cystoscopy might only reveal edematous, bullous, or erythematous mucosa (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of the SRCC component is associated with advanced-stage disease and worse outcomes. Its invasion pattern could spread laterally and widely without protruding through the surface (18). Cystoscopy might only reveal edematous, bullous, or erythematous mucosa (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, the SEER database does not provide information on chemotherapy, which was an obvious weakness of our study. Although some studies found that SRCC was resistant to systematic chemotherapy based on small sample sizes (18), some recent studies reported that adjuvant chemotherapy may be a potential component of effective treatment (21,22). Checkpoint-inhibitor drugs and genomic research offer hope to improve the treatment of bladder cancer (23).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the established concept of aggressiveness in the SRC ADK variant, we also tested for the effect of this histological subtype on CSM . Here, we showed that an important (31%) proportion of patients with ADK harbor SRC histology, a subtype known for its poor prognosis .…”
Section: Discussionmentioning
confidence: 96%
“…[22][23][24][25][26] Here, we showed that an important (31%) proportion of patients with ADK harbor SRC histology, a subtype known for its poor prognosis. [23][24][25][26] These patients had higher rates of NOC at RC, and also had worse CSM rates than other (non-SRC) ADK patients, and by extension UC patients. Conversely, non-SRC ADK histological subtype did not result in higher NOC rates or worse prognosis than UC.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] However, very recently, some authors reported a large series of patients with primary SRC carcinoma of the urinary bladder, underlining potentially curative cystectomy for these patients. 18 To plan the appropriate therapeutic strategy, a differential diagnosis between primary bladder adenocarcinoma and secondary adenocarcinoma from other primary sites is mandatory. Nevertheless, this differential diagnosis is often difficult and supported by few features.…”
Section: Case Discussionmentioning
confidence: 99%